2010
DOI: 10.1371/journal.pone.0011791
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β-Selective Agonists Stimulate Calcium Oscillations in Human and Mouse Embryonic Stem Cell-Derived Neurons

Abstract: Estrogens are used extensively to treat hot flashes in menopausal women. Some of the beneficial effects of estrogens in hormone therapy on the brain might be due to nongenomic effects in neurons such as the rapid stimulation of calcium oscillations. Most studies have examined the nongenomic effects of estrogen receptors (ER) in primary neurons or brain slices from the rodent brain. However, these cells can not be maintained continuously in culture because neurons are post-mitotic. Neurons derived from embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 96 publications
0
24
0
Order By: Relevance
“…Using reverse transcript (RT)-polymerase chain reaction (PCR) studies, others have shown the upregulation of VOCC expression in differentiated hESCs [23]. L-type channels are also expressed in NPs derived from human [25] and mouse ESCs [24].…”
Section: Expression Of Vocc In P7 Hesc Npsmentioning
confidence: 99%
“…Using reverse transcript (RT)-polymerase chain reaction (PCR) studies, others have shown the upregulation of VOCC expression in differentiated hESCs [23]. L-type channels are also expressed in NPs derived from human [25] and mouse ESCs [24].…”
Section: Expression Of Vocc In P7 Hesc Npsmentioning
confidence: 99%
“…Transmembrane ERs have been shown to activate diverse intracellular pathways, including protein kinase C (PKC) 20 , intracellular Ca 2+21,22 , cytosolic cAMP 23 , nitric oxide 24 , and MAPK 25 (Figure 1). For example, transmembrane ERα signaling through PI3K can result in cell proliferation and survival, while transmembrane ERβ signaling cause the influx of Ca 2+ in the cell, resulting in suppression of protein kinase C (PKC) signaling (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…These effects are inhibited by nifedipine, which suggests that the regulation of neural differentiation by might be mediated by LTCCs [93]. It has also been shown that dual ESCs [98].…”
Section: L-type Ca 2+ Channelsmentioning
confidence: 97%